Etude Des Effets Des Régulateurs De Croissance Sur La Les Stades De Prolifération Et De Développement De La Pomme De Terre (Solanum Tuberosum. L) In Vitro - Chahredine, Sadek; Ykhlef, Nadia (European Scientific Journal, ESJ, 2017)
The aim of this study is to determine the effects of different concentrations and combinations of the phytohormones, 1-naphthaleneacetic acid (NAA), and 6-benzylaminopurine (BAP): M1 (0.5 mg / l +1 mg / l), M2 (1 mg / l + 0.5 mg / l) , M3 (2 mg / l +2 mg / l), M4 (0.5 mg / l + l mg / l, NAA), M5 (1.0 mg / l + l mg / l , NAA), and M6 (2.0 mg / l + l mg / l, NAA). This study was carried out in dark condition on callus induction of potato plants (Solanum tuberosum L.) cultivars from potato tuber bud so as to demonstrate the role of light. The callus initiation begins after 7 days of incubation for all studied media. After two months of incubation, the better development of callus was noted in Spunta variety by using medium M1, M2, M3, and M6. The calluses took a compact structure of brown-white color for both varieties with a callus induction rate of 20- 40%. This was collected with kondor variety for M2 and (M3, M4, M5) media respectively and 10-30% for M4 (M1, M2, M3) for Spunta variety also. The highest fresh weight was recorded on M2 medium with 0.26g for Kondor variety and 0.93g for Spunta variety.